Umotywowanie kultu Larów w poetyckim micie Owidiusza, Fastii 2, 571-616 - Hartleb-Kropidło, Barbara (Uniwersytet Wrocławski. Pracownia Badań nad Tradycją Oralną, 2017)
In his poetic version of the Roman calendar titled Fasti Ovid presents, among varied astronomical data, a multitude of aetiological myths. One of these is a story of the Lares’ origin, otherwise unknown, in which the Roman poet depicts a colourful and pathetic story of the nymph Lara and her children, the Lares. The gods, which were previously celebrated at the Compitalia festival as tutelary deities, became on account of Augustus’ religious reforms the guardians of the whole City. The new function of the Lares was succoured by the poetic vision of Ovid, which appears to be rooted in ancient folklore.
Keywords: Lary; kult; rytuał; Owidiusz; mit